2021
DOI: 10.1002/jbm4.10530
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TGF‐β Increases Bone Volume and Strength in a Mouse Model of Osteogenesis Imperfecta

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…However, treatment with the 4 mg/kg dose resulted in sustained suppression of bone turnover, as shown by plasma Ocn levels. The latter effect is consistent with murine studies that show neutralizing TGF-β results in a decrease in bone turnover and an increase in bone mass ( 25 , 31 ). The effects on LS aBMD were more variable.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, treatment with the 4 mg/kg dose resulted in sustained suppression of bone turnover, as shown by plasma Ocn levels. The latter effect is consistent with murine studies that show neutralizing TGF-β results in a decrease in bone turnover and an increase in bone mass ( 25 , 31 ). The effects on LS aBMD were more variable.…”
Section: Discussionsupporting
confidence: 90%
“…Genotype and clinical severity are likely to have an influence on the response to therapy. Recent preclinical studies have shown that higher and more frequent dosing of anti–TGF-β therapy has a more significant effect on “normalizing” the coupling of bone resorption and bone formation, resulting in decreased bone remodeling, increased bone mineral density, and improved biomechanical properties ( 31 ). Furthermore, whereas mild and moderately severe murine models of collagen-related OI (G610C Col1a2 tm1.1Mcbr and Crtap –/– ) have shown a response to anti–TGF-β treatment, such response has not been observed in a more severe model ( Col1a1 Jrt/+ ) that has features of Ehlers-Danlos syndrome and OI ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also TGF-β binds to bone resorption and formation and recruits bone progenitor cells to the site of bone resorption. 39 TGF-β gene is located in the long arm of chromosome 19, and the gene is described as 5 SNPs, which are −800G/A (rs1800468) and −509C/T (rs1800469) promoter region and +896T/C (rs1982073), +915G/C (rs1800471), +29T/C (re1800470) coding region, respectively. Multiple studies have confirmed that TGF-β polymorphism is associated with disease susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) staining (C3206, Beyotime, Haimen, China) and staining of mineralized nodules with alizarin red (G1452, Solarbio, Beijing, China) were performed following the manufacturers' instructions. The proximal tibiae were analyzed using a 1500×1800‐μm region of interest (ROI) 150 μm from the growth plate in a grid‐like pattern along the ROI 34 . Five fields of each slide and five slides were randomly selected for analysis 35 …”
Section: Methodsmentioning
confidence: 99%